Interpretasi Progresif Hadis-Hadis Tema Perempuan: Studi Aplikasi Teori Qiraâ€™ah Mubadalah - Yulmitra Handayani; Mukhammad Nur Hadi (HUMANISMA : Journal of Gender Studies, 2020)
This study departs from a compilation of women-themed hadiths that were interpreted progresively by Faqihuddin in his book â€œ60 Hadis Hak-Hak Perempuan Dalam Islam:Teks dan Interpretasiâ€. Another starting used to study this topic is because women-themed hadiths tend to affrim menâ€™s superiority over women. Of the sixty hadith that have been interpreted, the researcher only chose a few hadiths, which are categorized in four major themes; the principle of male and female relations, womenâ€™s dignity, womenâ€™s choices and rights, and the relations of husband and wife. This study tries to learn and analyze how Faqihuddin applies the theory of qiraâ€™ah mubadalah (reading reciprocally) to these selected hadiths. The approach of this study are conceptual approach and content analysis approach. This study finds that qiraâ€™ah mubadalah is a progressive interpretation theory that relies on two things, the universal value of Islam and the substantial understanding of a text. Dialecting both things will be able to produce interpretations that carry the value of equality holistically. In the application level, Faqihuddin has internalized Islamic universalism in facilitating the substance of the text. When interpreting the hadith, Faqihuddin uses three types of interpretation; grammatical interpretation, historical interpretation and sociological interpretation. The first two types of interpretations are used to find the main text; the ground idea of the text. Meanwhile, sociological interpretations are used to reduce main thoughts and expand the meaning egalitarian.Â Kajian ini berangkat dari kompilasi hadis-hadis bertema perempuan yang diinterpretasikan secara progresif oleh Abdul Kodir dalam bukunya 60 Hadis Hak-Hak Perempuan Dalam Islam:Teks dan Interpretasi. Titik tolak lain yang digunakan untuk mengkaji topik ini adalah karena hadis-hadis bertema perempuan cenderungmeneguhkan superioritas laki-laki atas perempuan. Dari enam puluh hadis pilihan yang telah diinterpretasikan, peneliti hanya memilih beberapa hadis, yang terkategorikan dalam empat tema besar, yaitu prinsip relasi laki-laki dan perempuan, martabat perempuan, posisi dan hak-hak perempuan, dan relasi suami istri. Kajian ini bertujuan untuk mengetahui bagaimana Abdul Kodir mengaplikasikan teori qiraâ€™ah mubadalah-nya terhadap hadis-hadis pilihan. Pendekatan yang digunakan adalah pendekatan konseptual (conceptual approach) dan analisis isi (content analysis). Kajian ini menemukan bahwa qiraâ€™ah mubadalah adalah teori interpretasi progresif yangÂ  bertumpu pada dua hal, nilai universal Islam dan gagasan substansial sebuah teks. Mendialektikan keduanya akan mampu menghasilkan interpretasi yang mengusung nilai kesetaraan secara holistik. Dalam tataran aplikasi, Abdul Kodir telah mengintegrasikan universalisme Islam dalam memahami substansi teks.